Enhancing Indonesian EFL Students' Reading Comprehension of Report Texts through KWL Strategy with Multimedia: A Classroom Action Research - Azwar, Taufik Akbar; Ristiyanti, Surya Hazar; Puspita, Hilda (Universitas Negeri Gorontalo, 2024)
The significance of reading is undeniable in the English learning process. Thus, students need to be equipped with reading strategies to help them develop their English language. This study sought to improve students' reading comprehension and attitude through the use of know-want-learn (KWL) strategy in conjunction with multimedia. Classroom Action Research was employed involving 28 students in the ninth grade. Several instruments were utilized, i.e., reading comprehension tests, interview, observation checklist, and field notes. The mean scores of the reading tests increased from baseline (53) to cycle 2 (80.54) indicating that the result had achieved the criteria of success. It could be inferred that implementing KWL strategy with multimedia in the pre-reading stage enhanced students' reading comprehension. Two factors affecting the students' reading comprehension were identified, i.e., the teacher's participation and topic familiarity. The strategy was also found to foster students' participation and provide students with a concise framework to develop their English reading skills. This study therefore has contributed to the existing literature of English reading strategy and offered meaningful pedagogical implications for English teachers to harness the strategy incorporated with the use of current media such as pictures and videos to teach English reading.